The Effect of Good Corporate Governance on Financial Performance in LQ45 Companies Listed in Indonesian Stock Exchange - Muhammad, Nurkholis; Damayanti, Damayanti (Universitas Semarang, 2020)
This study is conducted to examine the effect of good corporate governance on financial performance. The variables used in this study are the board of commissioners, the board of directors, institutional ownership and the audit committee as independent variables, while the dependent variable is financial performance proxies with ROA. This study uses 14 consistent samples of LQ45 companies that met the sample criteria during 2014 to 2018. The sampling technique in this research is purposive sampling in order to obtain 70 observations. Because the classical assumption test gets problems in the autocorrelation test, the data are transformed using the cochrane orcutt method, so that the total observations become 69 observations. The data analysis technique utilizes multiple linear regression analysis. The results of this study indicate that the board of commissioners has a positive and significant effect on financial performance, while the board of directors has a significant negative effect on financial performance, and institutional ownership has a significant positive effect on financial performance, while the audit committee has a significant negative effect on financial performance. Based on the determination testing of variable of the board of commissioners, board of directors, institutional ownership and audit committee in the regression model, this study is able to explain the dependent variable of financial performance by 32.9%, while 67.1% is explained by other variables not examined in this study